Formation of Cytospheres and Neuronal Differentiation in New-Born Piglet Adrenal Cell Culture - Sidorenko, Olga S.; Bozhok, Galina A.; Legach, Evgeniy I.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(4):359–362.